Dari Kertas ke Kepastian: Peran Krusial Bukti Surat dalam Konflik Pertanahan - Gunawang, Gunawang; Mutmainna, Mutmainna (Jurnal Litigasi Amsir, 2024)
This study examines the power of evidentiary evidence in land dispute resolution in Indonesia, as well as the process of resolving land disputes through litigation. Using normative legal research methods, this study analyzes the role and significance of letter evidence in the context of Indonesia’s agrarian law, as well as the challenges faced in the digital era. Furthermore, this study also discusses the complexity of the litigation process in land disputes, including the stages of proof, the role of judges, and the social impact caused. The results of the study show that although letter evidence has strong evidentiary power, verification of the validity and consistency of court decisions is a crucial issue. The study also underscores the importance of judicial system reform and a holistic approach to land dispute resolution to achieve more comprehensive justice.